Comparison of BEAMing and Droplet Digital PCR for Circulating Tumor DNA Analysis. - O’Leary, Ben; Hrebien, Sarah; Beaney, Matthew; Fribbens, Charlotte; Garcia-Murillas, Isaac; Jiang, John; Li, Yuan; Bartlett, Cynthia Huang; Andre´, Fabrice; Loibl, Sibylle; Loi, Sherene; Cristofanilli, Massimo; et al. (Clinical Chemistry, 2019)
BACKGROUND: Circulating tumor DNA (ctDNA) assays are increasingly used for clinical decision-making, but it is unknown how well different assays agree. We aimed to assess the agreement in ctDNA mutation calling between BEAMing (beads, emulsion, amplification, and magnetics) and droplet digital PCR (ddPCR), 2 of the most commonly used digital PCR techniques for detecting mutations in ctDNA. METHODS: Baseline plasma samples from patients with advanced breast cancer enrolled in the phase 3 PALOMA-3 trial were assessed for ESR1 and PIK3CA mutations in ctDNA with both BEAMing and ddPCR. Concordance between the 2 approaches was assessed, with exploratory analyses to estimate the importance of sampling effects. RESULTS: Of the 521 patients enrolled, 363 had paired baseline ctDNA analysis. ESR1 mutation detection was 24.2% (88/363) for BEAMing and 25.3% (92/363) for ddPCR, with good agreement between the 2 techniques ( 0.9l; 95% CI, 0.85– 0.95). PIK3CA mutation detection rates were 26.2% (95/363) for BEAMing and 22.9% (83/363) for ddPCR, with good agreement ( 0.87; 95% CI, 0.81– 0.93). Discordancy was observed for 3.9% patients with ESR1 mutations and 5.0% with PIK3CA mutations. Assessment of individual mutations suggested higher rates of discordancy for less common mutations (P 0.019). The majority of discordant calls occurred at allele frequency 1%, predominantly resulting from stochastic sampling effects. CONCLUSIONS: This large, clinically relevant comparison showed good agreement between BEAMing and ddPCR, suggesting sufficient reproducibility for clinical use. Much of the observed discordancy may be related to sampling effects, potentially explaining many of the differences in the currently available ctDNA literature.